PROGRAM PEMELIHARAAN JALAN NASIONAL DI PROVINSI SUMATERA UTARA - Sartika, Andriyani Indah; Mulyono, Agus Taufik (Jurnal Transportasi, 2014)
Abstract  Existing condition of national roads in the Province of North Sumatera at the end of 2014 has not been fully optimized, with the proportion of road conditions that fall into either good and medium categories still had a significant decrease each year. In addition, the width of pavement is still dominated by the class of small roads (less than 7 m). This study aimed to evaluate the effectiveness of the national road maintenance program in the Province of North Sumatera from 2012 until 2014. The effectiveness was evaluated by using the modified Importance Performance and the Customer Satisfaction Index. This results indicates that the outputs generated by the road handling in this study is somewhat different compared to those implemented by the Directorate General of Highways, especially in the handling of capacity expansion. Key words: road conditions, road maintenance, road width, capacity expansion  Abstrak Kondisi existing jalan nasional di Provinsi Sumatera Utara akhir tahun 2014 belum sepenuhnya optimal, dengan proporsi kondisi jalan berkategori baik dan sedang masih mengalami penurunan yang signifikan setiap tahunnya. Selain itu lebar perkerasan jalan masih didominasi oleh kelas jalan kecil (kurang dari 7 m). Studi ini bertujuan untuk mengevaluasi efektivitas program pemeliharaan jalan nasional di Provinsi Sumatera Utara yang telah berjalan mulai tahun 2012 hingga tahun 2014. Efektivitas dievaluasi dengan menggunakan metode Importance Performance Analysis (IPA) dan Customer Satisfaction Index (CSI) yang dimodifikasi. Hasil studi ini menunjukkan bahwa output jenis penanganan yang dihasilkan studi ini agak berbeda dengan program yang dilaksanakan oleh Direktorat Jenderal Bina Marga, khususnya pada penanganan penambahan kapasitas jalan. Kata-kata kunci: kondisi jalan, pemeliharaan jalan, lebar jalan, penambahan kapasitas